2000
DOI: 10.1046/j.1432-1327.2000.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome cM from Synechocystis 6803

Abstract: Based on DNA sequence data a novel c-type cytochrome, cytochrome c M , has been predicted to exist in the cyanobacterium Synechocystis 6803. The precursor protein consists of 105 amino acids with a characteristic heme-binding motif and a hydrophobic domain located at the N-terminal end that is proposed to act as either a signal peptide or a membrane anchor. For the first time we report the detection of cytochrome c M in Synechocystis 6803 using Western blot analysis. The soluble portion cytochrome c M has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…As shown in Table 1 , the molecular mass of Cyt c M deduced from the gene sequence (8.3 kDa) and that calculated by SDS–PAGE (7.9 kDa) is similar to those reported for Synechocystis Cyt c 6 and Pc [7,23]. The midpoint redox potential value of Cyt c M determined in this work (+150 mV, at pH 7) is very similar to that previously described for the modified Cyt c M [2], but significantly lower than that reported for Cyt c 6 and Pc (+350 mV, at pH 7) [23,24].…”
Section: Resultssupporting
confidence: 89%
“…As shown in Table 1 , the molecular mass of Cyt c M deduced from the gene sequence (8.3 kDa) and that calculated by SDS–PAGE (7.9 kDa) is similar to those reported for Synechocystis Cyt c 6 and Pc [7,23]. The midpoint redox potential value of Cyt c M determined in this work (+150 mV, at pH 7) is very similar to that previously described for the modified Cyt c M [2], but significantly lower than that reported for Cyt c 6 and Pc (+350 mV, at pH 7) [23,24].…”
Section: Resultssupporting
confidence: 89%
“…The physiological data presented above indicated that electron transfer to PSI could take place in the absence of [17] have revealed in vitro a redox potential that would be too low for such a function in our present understanding of electron transfer from plastoquinone (PQ) to the PSI reaction centre. The question on how electrons transfer to PSI in petJ mutant grown in the absence of copper ion remains to be answered in detail.…”
Section: Psi Function In the Wt And The Petj-null Mutantmentioning
confidence: 99%
“…Although studies with soluble CtaC indicate that Cyt c M is not absolutely required for electron transfer [18][19][20], it may promote binding or act as a redox mediator between soluble electron carriers and COX [26]. Although the measured redox potential (E m ) of soluble Cyt c M was only 150 mV [27] (which would raise a problem for its reduction by Cyt f (cytochrome f ), E m ≈ 330 mV), membrane localization and/or the presence of other COX subunits could potentially increase this to allow Cyt c M to act as a redox mediator.…”
Section: The Aa 3 -Type Coxmentioning
confidence: 97%